Interrogating the Impassable: A Case Series and Literature Review of Unilateral SPECT-CT Groin Visualization in Men With Penile Cancer - O'Brien, Jonathan S.; Teh, Jiasian; Kelly, Brian D.; Chen, Kenneth; Manning, Todd; Furrer, Marc; Chee, Justin; Lawrentschuk, Nathan (Frontiers in Surgery, 2022)
Penile squamous cell carcinoma (SCC) is a rare malignancy which is known to invade local inguinal lymph nodes prior to progressing to the pelvis. Dynamic sentinel lymph node biopsy (DLSNB) is a standard for the minimally invasive assessment of lymphadenopathy in patients with subclinical groin metastasis. Hybrid 99mTc Single-Photon Emission Computed Tomography (SPECT-CT) has been shown to increase the accuracy of identifying first draining ‘sentinel’ nodes (SN). Unilateral inguinal visualization on SPECT-CT is a rare presentation which may increase the likelihood of a false negative sentinel node biopsy. Retrospective analysis from three penile cancer uro-oncologists in Melbourne, Australia identified 78 groins undergoing DSLNB for intermediate/high risk primary disease. Unilateral SPECT-CT results were observed in 4 patients suggesting a functional pattern of lymph diversion. Analysis confirmed malignancy (n=2), sarcoidosis (n=1), and evidence of local inflammation in SPECT-CT negative groins. Findings re-iterate the role of SPECT-CT a pre-operative adjunct which cannot replace experienced multimodal groin assessment. Unilateral SN on pre-operative SPECT-CT in men with intermediate/high-risk penile SCC should elicit a higher degree of clinical suspicion. We recommend a low threshold for recommending radical inguinal lymph node dissection (ILND) for groins refractory to minimally invasive assessment.